1969
DOI: 10.1128/jb.98.2.494-501.1969
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Activity of Endotoxin II. Mechanism of the Phenomenon in BCG-infected Mice

Abstract: The mechanism of the hypoglycemic activity of endotoxin in hyperreactive BCG mice was investigated. The mechanism was found to be an inhibition of the synthesis of glucose from noncarbohydrate sources. The possibilities of an induced hypermetabolic state and an induced release of insulin in response to endotoxin as causes for the hypoglycemic response were essentially ruled out. In addition, no clear-cut evidence of an insulin-like action by endotoxin was found in the in vivo setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…In the previous report (43), we found a decrease in the activity of G-6-Pase in endotoxin-poisoned mice after 18 hr, and this result coincided with that reported by McCallum and Berry (24). However, hepatic phosphorylase activity in the poisoned mice was appreciably higher than that in control mice after 2 hr, whereas its activity after 18 hr was not significantly different from that in the control fasted mice (37). Another study (41) in our laboratory has shown that in mice injected intraperitoneally with live Vibrio parahaemolyticus (pathogenic strain), the hepatic phosphorylase and G-6-Pase activities showed a tendency similar to the rise and fall in the blood sugar level although the pathogen exacerbated a heat-stable hemolytic toxin (47) showing lethality to mice, in addition to endotoxin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the previous report (43), we found a decrease in the activity of G-6-Pase in endotoxin-poisoned mice after 18 hr, and this result coincided with that reported by McCallum and Berry (24). However, hepatic phosphorylase activity in the poisoned mice was appreciably higher than that in control mice after 2 hr, whereas its activity after 18 hr was not significantly different from that in the control fasted mice (37). Another study (41) in our laboratory has shown that in mice injected intraperitoneally with live Vibrio parahaemolyticus (pathogenic strain), the hepatic phosphorylase and G-6-Pase activities showed a tendency similar to the rise and fall in the blood sugar level although the pathogen exacerbated a heat-stable hemolytic toxin (47) showing lethality to mice, in addition to endotoxin.…”
Section: Discussionsupporting
confidence: 91%
“…The activities of hepatic phosphorylase and G-6-Pase were observed to have a similar tendency to the level of blood sugar. Endotoxicosis depresses both in vivo gluconeogenesis and glycogenesis in the liver (4,12,13,22,25,37). In the previous report (43), we found a decrease in the activity of G-6-Pase in endotoxin-poisoned mice after 18 hr, and this result coincided with that reported by McCallum and Berry (24).…”
Section: Discussionsupporting
confidence: 91%
“…Whether this loss of carbohydrate is due to an increase in glycolysis or impaired gluconeogenesis has been unclear. Berry and coworkers (3,4) and Shands et al (13) suggested that the carbohydrate loss is due to the failure of the endotoxin-poisoned animals to convert gluconeogenic intermediates into glycogen. Specifically, Berry et al (3) have shown that endotoxin prevents induction of PEP carboxykinase by cortisone, thus confirming by direct enzyme assay impaired conversion of glyconeogenic intermediates to PEP.…”
Section: Discussionmentioning
confidence: 99%
“…More recently Shands et al (13) presented data indicating that the major defect in glucose metabolism in BCG-vaccinated mice given endotoxin may be in synthesis of glucose from noncarbohydrate sources. This interpretation would agree with the data on PEPCK presented by Berry and co-workers (3).…”
mentioning
confidence: 99%
“…On the other hand, Woods et al (53) showed that Salmonella endotoxin exerted a stimulatory effect on tumor glycolysis similar to the action of insulin. Shands et al (42), however, reported that no clear-cut evidence for this insulin-like action by endotoxin was observed in the in vivo setting.…”
mentioning
confidence: 98%